2019
DOI: 10.1111/pai.13058
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and allergic diseases in urban and rural communities from the South African Food Allergy cohort

Abstract: This study describes and compares allergic diseases and sensitization in urban and rural children in the SAFFA study cohort as well as infant feeding patterns and nutritional status. We assessed the relationship between nutritional status, breastfeeding, complementary feeding patterns, and atopic diseases including aeroallergen and food allergen sensitization, self-reported atopic dermatitis, allergic rhinitis, asthma, and challenge-proven food allergy (FA).Methodology: A total of 1185 urban and 398 rural todd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
40
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 22 publications
(28 reference statements)
5
40
1
Order By: Relevance
“…[15][16][17] Farming or urban/rural exposure studies have been performed in multiple disparate environments, documenting and adding detail to the protective effects seen in rural settings. 12,13,[18][19][20][21][22][23][24][25][26][27] In most studies contact with farm animals, such as livestock, was protective, [21][22][23][24][28][29][30][31] and in others a role for ingestion of unpasteurized cow's milk was protective. [32][33][34] The role of each of these effects in disparate communities across the globe and the interactions between these effects and others, such as a family history of allergy and asthma, family size, maternal smoking, diet, physical activity, vitamin D and sunlight exposure, antibiotic exposure, birth by cesarean section, and probiotic and prebiotic exposure, remains controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17] Farming or urban/rural exposure studies have been performed in multiple disparate environments, documenting and adding detail to the protective effects seen in rural settings. 12,13,[18][19][20][21][22][23][24][25][26][27] In most studies contact with farm animals, such as livestock, was protective, [21][22][23][24][28][29][30][31] and in others a role for ingestion of unpasteurized cow's milk was protective. [32][33][34] The role of each of these effects in disparate communities across the globe and the interactions between these effects and others, such as a family history of allergy and asthma, family size, maternal smoking, diet, physical activity, vitamin D and sunlight exposure, antibiotic exposure, birth by cesarean section, and probiotic and prebiotic exposure, remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…11 We have previously reported on a significant difference in the prevalence of aeroallergen sensitization, eczema, asthma, and allergic rhinitis (AR), as well as FS and food allergy, between urban and rural South African children 12 and the interactions between nutritional status and infant feeding in this cohort. 13 We assessed for differences in environmental factors between urban and rural communities and for associations with aeroallergen sensitization, allergic diseases, FS, and challengeproved food allergy. Environmental factors assessed included those that affect the microbiome (mode of delivery, exposure to livestock and pets, consumption of antibiotics and probiotics, and antihelminth treatment) and dietary factors, including consumption of unpasteurized milk, natural and medicinal probiotics, fast foods, fried and microwaved meats, and fruits and vegetables.…”
mentioning
confidence: 99%
“…This is the first study in Africa to show such a strong gradient in asthma risk by place of birth. Previous studies have been mostly crosssectional and conducted in either rural or urban settings, and therefore focusing on current residence; these have shown that the prevalence of asthma is lower among rural residents compared to urban residents (6,7,10).…”
Section: Discussionmentioning
confidence: 99%
“…There is a scarcity of data on asthma risk factors from Africa. The few studies reported have suggested that current residence in urban areas is associated with a higher risk of asthma than rural residence (10,11). Other risk factors, similar to those in HICs, include maternal smoking (12,13), maternal history of asthma (14), childhood atopic sensitisation (11,15) and history of allergy (14,16).…”
Section: Introductionmentioning
confidence: 99%
“…It is a tradition of the editorial to comment on three original scientific communications published in this issue. Maresa Botha and colleagues have taken advantage of the large South African Food Allergy cohort (SAFFA), which allowed earlier identification of the large difference in food allergy prevalence between rural and urban communities, to explore the role of early infant feeding and nutrition . Patterns of breastfeeding were statistically different, with longer breastfeeding in the rural community.…”
mentioning
confidence: 99%